Disentangling the genetic overlap between ischemic stroke and obesity - Ren Yang; Tangfeng Zhang; Feng Han (Diabetology & Metabolic Syndrome)
Abstract Objective Obesity has been recognized as a risk factor for cerebrovascular diseases, with observational studies suggesting a heightened incidence of stroke. However, the genetic epidemiology field has yet to reach a consensus on the causal relationship and genetic overlap between ischemic stroke (IS) and obesity. Methods We utilized linkage disequilibrium score regression, high-definition likelihood, and local analysis of variant associations to assess the genetic correlation between body mass index (BMI) and IS. Bidirectional Mendelian randomization was employed to infer causality. We identified shared risk single nucleotide polymorphisms (SNPs) through cross-trait meta-analyses and estimated heritability using summary statistics. Summary-data-based Mendelian randomization (SMR) was applied to explore potential functional genes. Results Our analysis revealed a significant positive genetic correlation between BMI and IS, supporting a causal link from BMI to IS. Cross-trait analysis yielded 9 and 16 shared risk SNPs for IS and small vessel stroke (SVS), respectively. We observed a notable enrichment of SNP heritability for IS and BMI in brain tissues, suggesting tissue-specific influences. The genes shared between the traits were predominantly involved in brain development, synaptic electrical activity, and immunoregulation. Notably, our SMR analysis identified the risk genes CHAF1A, CEP192, ULK4, CYP2D6, AS3MT, and WARS2 across the majority of the 14 enriched tissues shared by both traits. Conclusion Our study uncovered a significant genetic correlation and identified shared risk SNPs between BMI and IS. The identification of CHAF1A, CEP192, ULK4, CYP2D6, AS3MT, and WARS2 as potential functional genes common to both obesity and IS enriched our understanding of their genetic interplay, potentially advanced our grasp of their pathogenesis and therapeutic targets.